Proficiência em língua inglesa e práticas sócio-educacionais: um estudo com alunos do ensino médio da rede estadual paulista - Jesus, Mônica Raimunda de (2010)
This study aims to examine the relationship between proficiency in English and previous school experiences, as well as personal characteristics, family ambience and social experiences in English Language, of students who attended the last year of High School in 2008. The research was conducted in two public schools of the state of São Paulo. As basic procedure for data collection, questionnaires and a test of proficiency in English language were applied to High School students of the schools surveyed. Data analysis was based on the theories of Bourdieu (1971, 1982, 1989, 1998, 2007) about cultural and social capital, as we propose to understand the practices in English in the social educational experience of research participants, which has determined or not a satisfactory or unsatisfactory assimilation of the English Language. Besides, we analyse the activities involving the English language based on the contributions of the same author on the social construction of taste. We have found, using data collected, that some social and educational practices of last year High School students of the same social class are determinants for some of these students who obtain better performance in English than the majority of students. In the test of English proficiency, from the 99 surveyed students, 6 had a better result than average, 16 obtained an average performance and 77 underperformed. These data show that although the students attended at least seven years of English classes, the skill level of the majority is very low, which, on one side, reinforces the poor quality of Brazilian schools in general, and it indicates that Foreign Language education is also a factor in this lack of quality: so much so that, when comparing the results of students from two schools and their rates of assessment (SARESP) that differ from each other, the levels of proficiency in English were similar, which made us leave the initial goal of mutual comparison between the results of students in each school. As regards the relationship between family ambience, educational and social experiences and levels of proficiency, we found the following results: the existence of a family member who knows English seems to be insignificant in increasing proficiency; social experiences (use of the internet, habits of reading in English and watching dubbed movies) show that even if one does not know whether the habit leads to the best proficiency or the best proficiency leads to the habits, the fact is that students who had higher proficiency in English read and watched more subtitled films, which seems to reinforce the view that education does nothing more than reinforce the culture obtained outside school. With regard to school experience, the most significant finding concerns the high number of students with low proficiency and that were failed in High School, which seems to confirm that this group of students is destined to failure in all activities and school subjects